The effect of barbiturates in porphyria turcica - Doğramacı, İhsan and Özand, Pınar and Müftü, Yunus and Ergene, Turhan (The Turkish Journal of Pediatrics, 1963)
Case histories of three patients with porphyria turcica are presented. Two patients manifested the disease in a quiescent state, one was acutely ill. All three volunteered for experimental treatment with a porphyria-inducing drug: seconal, an allylbarbiturate. In no case did the drug aggravate existing symptoms or induce new ones nor did it produce any change in the excretory pattern of porphyrins. The biochemical pathology of the drug-induced porphyrias, in particular the effect of the barbiturate analogue, sedormid, on porphyrin metabolism, is discussed in some detail.